Alterações nas propriedades químicas de solos tratados com diferentes doses do herbicida glifosato - Silva, Marcela Arfelli (2013)
The great need for high productivity in crops has caused frequent and intensive use of pesticides, which are often applied indiscriminately, generating risks for the environment and, consequently, severe damage to human health. Thus, the aim of this study was to evaluate the physical and chemical changes in soil, weed control, caused by different concentrations of glyphosate. The experiment was conducted at Universidade Federal Tecnológica do Paraná - Campus Londrina, where 15 plots of 1m2 and indentified the weeds. In each plot were applied concentrations of glyphosate T1(0.96 kg i.a.ha-1); T2(1.92 kg iaha-1) ;T3(3.84 kg iaha-1) and during 14 days after the application was analyzed mortality weed. An initial sample and a soil sample collected 14 days after application, were sent to a commercial laboratory for analysis of calcium, magnesium, potassium, organic matter, total nitrogen, phosphorus, cation exchange capacity, pH (in CaCl2 and in H2O). At the same time, in the intercalary days, samples were collected from all the plots for individual physical-chemical analysis in the laboratory of the Universidade Federal Tecnológica do Paraná - Campus Londrina, to determine levels of calcium, magnesium, ammonia, nitrite, nitrate, phosphorus. These tests were conducted using the methods of Soil Test Kit Polikit (Manufacturered by Alfakit) which were subjected to analysis of variance, with comparison by Tukey test at 5% significance. It was possible to obtain satisfactory control in species Emilia fosbergii Nicolson, Croton glandulosus, Sida rhombifolia L., Rhynchelytrum repens, Richardia brasiliensis Gomes, exotic plant and Brachiaria lantaginea. Already species, Parthenium hysterophorus, Ipomoea hederifolia, Sonchus oleraceus, Cenchus. echinatus, were resistant to glyphosate. All treatments with glyphosate caused changes in physico-chemical soil. All parameters proposed for analysis with Polikit Soil significant difference in relation to collections, but did not differ significantly with respect to the applied treatments. It can be stated that the analysis proposed in the study can be instituted as monitoring parameters in modifying physical and chemical characteristics of the soil.